Nanoscale Particulate Matter from Urban Traffic Rapidly Induces Oxidative Stress and Inflammation in Olfactory Epithelium with Concomitant Effects on Brain - Cheng, Hank (Environ Health Perspect, 2016)
BACKGROUND: Rodent models for urban air pollution show consistent induction of inflammatory responses in major brain regions. However, the initial impact of air pollution particulate material on olfactory gateways has not been reported. OBJECTIVE: We evaluated the olfactory neuroepithelium (OE) and brain regional responses to a nanosized subfraction of urban traffic ultrafine particulate matter (nPM, < 200 nm) in vivo, ex vivo, and in vitro. METHODS: Adult mice were exposed to reaerosolized nPM for 5, 20, and 45 cumulative hours over 3 weeks. The OE, the olfactory bulb (OB), the cerebral cortex, and the cerebellum were analyzed for oxidative stress and inflammatory responses. Acute responses of the OE to liquid nPM suspensions were studied with ex vivo and primary OE cultures. RESULTS: After exposure to nPM, the OE and OB had rapid increases of 4-hydroxy-2-nonenal (4-HNE) and 3-nitrotyrosine (3-NT) protein adducts, whereas the cerebral cortex and cerebellum did not respond at any time. All brain regions showed increased levels of tumor necrosis factor-α (TNFα) protein by 45 hr, with earlier induction of TNFα mRNA in OE and OB. These responses corresponded to in vitro OE and mixed glial responses, with rapid induction of nitrite and inducible nitric oxide synthase (iNOS), followed by induction of TNFα. CONCLUSIONS: These findings show the differential time course of oxidative stress and inflammatory responses to nPM between the OE and the brain. Slow cumulative transport of inhaled nPM into the brain may contribute to delayed responses of proximal and distal brain regions, with potential input from systemic factors. CITATION: Cheng H, Saffari A, Sioutas C, Forman HJ, Morgan TE, Finch CE. 2016. Nanoscale particulate matter from urban traffic rapidly induces oxidative stress and inflammation in olfactory epithelium with concomitant effects on brain. Environ Health Perspect 124:1537–1546; http://dx.doi.org/10.1289/EHP134